The Effectiveness of Dual Roles for Style Attendants at Hotel WXY - Kristiari, Oniek; Arthini, Ni Nyoman Suci; Indrayani, I Gusti Ayu Putu Wita (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study was motivated by guest complaints about the housekeeping department at Hotel WXY due to the lack of accuracy of the style attendant in handling work, which was caused by the dual role they had. This study aims to evaluate the effectiveness of the dual role. Data were collected through interviews with two style attendants and a supervisor, using three indicators of work effectiveness from Hasibuan: work quality, work quantity, and time utilization. The results of the study showed that the dual role was not yet effective in terms of work quality, but was quite effective in terms of work quantity and time utilization. This study is expected to improve the effectiveness of the style attendant's work, especially in terms of work quality